The role of knowledge management and product innovation in enhancing business performance: the mediating effect of absorptive capacity - Putri, Dewi Rama; Maulina, Shinta; Afifah, Alya Nurul; Hasan, Zainul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to analyze the impact of Knowledge Management (KM) and Product Innovation on Business Performance, with Absorptive Capacity acting as a mediating variable. Focusing on SMEs in the food and beverage sector in West Java, Indonesia, the research employs a quantitative explanatory approach using Structural Equation Modeling (SEM) on data from 400 respondents. The findings reveal that Product Innovation significantly enhances strategic Absorptive Capacity, which in turn strengthens financial control and positively affects Business Performance. In contrast, Knowledge Management shows no direct or mediating impact on either Absorptive Capacity or Business Performance. These results emphasize the importance of the indirect pathway from Product Innovation to financial control as a key mechanism for improving organizational performance. The study contributes theoretically by integrating critical variables into a unified conceptual framework and offers practical insights for innovation-driven strategies to boost SME competitiveness in the digital era.